ANALISIS PROFIL USAHA EKONOMI DESA SIMPAN PINJAM (UED SP) BIDANG PERKEBUNAN DI DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Rini Arvika Sari (Inovbiz: Jurnal Inovasi Bisnis, 2018)
This research aimed to know the economic effort’s profile saving and loan village (UED SP) about plantation in Bantan Tengah district of Bengkalis regency. The background of the research was UED SP program as the government effort to reduce destitute society in economic policy continuously. Meanwhile there were some obstacle in implementation of UED SP activities were not effective in the real implementation .it can be proven from the arrear every month and abuse fund from UED SP members. The objectives of the research were to know the profile comparison of UED SP from every effort that conducted by the profiler. This research was implemented in Bantan Tengah and used qualitative descriptive method to collect the information from UED SP Program. The result showed that there is significant effect of UED SP program toward receiver’s income. It can be concluded that there was a significant effect increasing of UED SP profiler’s income. The significant factors that influence the income of profiler UED SP such as education level, effort experience, family financial burden.  In addition the highest participation of the society in every steps in program is the most important thing to determine the successfully of the program to increase social welfare of society in Bantan village Bengkalis regency.